2018
DOI: 10.1007/s11060-018-2811-y
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and requirements in patients with brain tumours and their relatives

Abstract: Patients with brain tumours face a number of medical and social challenges. Previous studies have shown that these patients and their relatives need a high level of patient-oriented information and counselling. However, these needs are often underestimated. In this single-centre cross-sectional study, we evaluated, for the first time, the information needs of patients with brain tumours and their relatives depending on diagnosis, age and level of education. The participants were interviewed using pre-specified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Four studies (Halkett et al, 2015;Langbecker & Yates, 2016;Reinert et al, 2018;Renovanz et al, 2017) were identified that quantified unmet supportive care needs of persons diagnosed with rare CNS cancer (i.e., primary brain tumour). Unmet needs were highest in the psychological domain (24-56%), followed by the physical and daily living domain (15-50%) and the healthcare system and information domain (15-30%), and these needs were reported throughout the whole disease trajectory.…”
Section: Unmet Needs Of Patients With Rare Cns Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies (Halkett et al, 2015;Langbecker & Yates, 2016;Reinert et al, 2018;Renovanz et al, 2017) were identified that quantified unmet supportive care needs of persons diagnosed with rare CNS cancer (i.e., primary brain tumour). Unmet needs were highest in the psychological domain (24-56%), followed by the physical and daily living domain (15-50%) and the healthcare system and information domain (15-30%), and these needs were reported throughout the whole disease trajectory.…”
Section: Unmet Needs Of Patients With Rare Cns Cancermentioning
confidence: 99%
“…D.V. Oberoi, White, Seymour, Prince, et al, 2017b;O'Brien et al, 2017;Pateman et al, 2015;Peeters et al, 2018;Philp et al, 2017;Piil et al, 2018;Pongthavornkamol et al, 2019;Putri et al, 2018;Reinert et al, 2018;Renovanz et al, 2017;Richardson et al, 2015;Rietveld et al, 2018;Saroa et al, 2018;Shun et al, 2018;Singh et al, 2017;Skoogh et al, 2013;Smith et al, 2013; W.K. So et al, 2019;Sperling et al, 2014;Vermeer et al, 2015;Wells et al, 2015;Williamson et al, 2018;Wolin et al, 2017;Yu et al, 2017;Zeng et al, 2017).Studies were conducted in Europe (N = 19), Australia/New Zealand (N = 13), Asia (N = 9), Canada (N = 9), United States (N = 5) and Africa (N = 2).…”
mentioning
confidence: 99%
“… 19 Similarly, according to a study by Ghoshal et al , 20 the patients felt that knowing a diagnosis and prognosis may help them to be prepared, plan additional treatment, anticipate complications, and plan for the future and family. The strong desire among caregivers to protect the physical and psychological well-being of patients was noted by Victor et al 21 while the majority of the patients in a study by Reinert et al 22 expressed the need for more information preferably through a personal, face-to-face meeting. This was supported by nearly two-thirds of patients and one-fourth of caregivers who reported that prognostic information was important according to Diamond et al 23 Disclosing more detailed information to terminally ill cancer patients contributed to a better quality of communication, irrespective of the stage of disclosure as estimated by two studies.…”
Section: Resultsmentioning
confidence: 98%
“…Full texts of 126 articles were screened. A total of 27 studies fulfilled eligibility criteria and were thus eligible for inclusion in this systematic review and meta‐analysis 2,3,8‐32 . Table 1 shows the characteristics of included studies with the prevalence of collusion.…”
Section: Resultsmentioning
confidence: 99%